COMPARISON OF ENVIRONMENTAL LAW ENFORCEMENT WITH THE CONCEPT OF HUMAN RIGHTS AND CRIMINAL LAW - Sarah Furqoni; Jelly Leviza (LEX SOCIETAS: Journal of Law and Public Administration, 2024)
There are at least four dimensions that can affect the quality of environmental law enforcement, namely the existence of real environmental laws, violators of the law themselves, victims (society), and law enforcement officers, where the four dimensions are mutually influential and take place in a single political, social, economic, and cultural structure in certain circumstances. Environmental problems are complex and interesting problems to study in depth, this is what attracts the author to conduct research on criminal policies that exist in efforts to enforce environmental law in Indonesia. The type of legal research that the author uses in compiling this legal writing is the normative juridical research type. In the context of environmental management based on the Law on Environmental Protection and Management, environmental law enforcement can be carried out in two ways, namely preventively and repressively. Preventive environmental law enforcement is carried out through supervision, while repressive law enforcement is carried out through the application of sanctions. Supervision and the application of sanctions are aimed at achieving community compliance with environmental legal norms